Temporal changes in the extractability, bioaccessibility and biodegradation of target hydrocarbons in soils from former refinery facilities. (May 2021) - Towell, Marcie G.; Vázquez-Cuevas, Gabriela M.; Bellarby, Jessica; Paton, Graeme I.; Coulon, Frédéric; Pollard, Simon J.T.; Semple, Kirk T.
Abstract: This study investigated the extractability, bioaccessibility and biodegradation of 14 C-phenanthrene and 14 C-octacosane in two soils from former oil refinery facilities over 341 days. The impact of biostimulation and bioaugmentation treatments was also evaluated. At 0, 31, 62, 124 and 341 days, the loss and extractability (using dichloromethane, methanol:water and hydroxypropyl- β -cyclodextrin (HPCD)) of the 14 C-hydrocarbons were measured. Further at each time point, the mineralisation of the 14 C-hydrocarbons was measured respirometrically under the different conditions. In general, extractions with methanol: water and HPCD were similar for both hydrocarbons in the different treatments; however, these values were less that those measured with DCM. Overall, significantly higher ( p  ≤ 0.05) amounts of 14 C-phenanthrene were lost, readily extracted and mineralised in the soils, with treatments having little impact upon the degradation of this hydrocarbon over 341 days. Conversely, bioaugmentation significantly increased the loss of 14 C-octacosane residues from soils and sustained degradation after 31 days. Surprisingly, HPCD and methanol:water both under-predicted the extent to which the contaminants were degraded at each time point. Determining the likelihood of effective biodegradation by the stimulation of indigenous microorganisms or through bioaugmentation needs to be assessed by both chemical and biological measurements of bioaccessibility, rather than just by that which is totally extractable from soil. However, soils which have high loadings of organic matter and/or organic contaminants may prevent accurate assessment of contaminant bioaccessibility, as measured by HPCD. Graphical abstract: Image 1 Highlights: Phenanthrene was readily degraded in the soil irrespective of the treatments. OCT was degraded more effectively by bioaugmentation hence this approach might be more suitable for this type of hydrocarbons. Prediction of biodegradation potentials should use an integrated biochemical approach to provide realistic scenarios. HPCD underestimates hydrocarbon bioaccessibility in soil with large amounts of SOM and high levels of contamination.